Premature mortality in autism spectrum disorder - Hirvikoski, T.; Mittendorfer-Rutz, E.; Boman, M.; Larsson, H.; Lichtenstein, P.; Bölte, Sven (Royal College of Psychiatrists, 2016)
Background: Mortality has been suggested to be increased in autism spectrum disorder (ASD). Aims: To examine both all-cause and cause-specific mortality in ASD, as well as investigate moderating role of gender and intellectual ability. Method: Odds ratios (ORs) were calculated for a population-based cohort of ASD probands (n = 27 122, diagnosed between 1987 and 2009) compared with gender-, age-and county of residence-matched controls (n = 2 672 185). Results: During the observed period, 24 358 (0.91%) individuals in the general population died, whereas the corresponding figure for individuals with ASD was 706 (2.60%; OR = 2.56; 95% CI 2.38-2.76). Cause-specific analyses showed elevated mortality in ASD for almost all analysed diagnostic categories. Mortality and patterns for cause-specific mortality were partly moderated by gender and general intellectual ability. Conclusions: Premature mortality was markedly increased in ASD owing to a multitude of medical conditions.